Bahasa Inggris - Jihat Nurrahman; Hodairiyah Hodairiyah; Ray Suryadi (Universitas Musamus Merauke, 2022)
This research aimed at explaining the implementation of Student Team Achievement Division (STAD) technique in enhancing the students’ reading comprehension. The study was a classroom action research. The research was carried out in a cyclic process. The subject of this study were the students of semester I Mathematics Education Study Program STKIP PGRI Sumenep in the academic year 2022/2023. The data were collected through a number of instruments namely observation sheets and field-note analyzed qualitatively, and the result of the quizzes were analyzed quantitatively. The findings show that first, there was a significant improvement on the students’ reading achievement after being taught by using STAD Technique. Second, there was a good improvement on the students’ responsibility in learning the lesson and the students’ learning motivation. Based on the quizzes given at the end of each cycle, there was a significant improvement in the students’ reading comprehension. In the first cycle, the average score gained by the students was only 59%, in the second cycle, the average score improved at the level of 77%, and in the last cycle, the students’ average score was 88%. A conclusion can be drawn then the implementation of the STAD technique gave contribution positively in enhancing the students’ reading comprehension